On Hair Color in France - Gilkerson, Ellen; Lamport, Leslie (Annals of Improbable Research, 2004)
While traveling in France, Gilkerson and I observed many blonde women, but almost no blonde men. Suspecting that we had stumbled upon a remarkable scientific discovery, we endured several weeks of hardship visiting the auberges and restaurants of France to gather data. After several years of analysis and rigorous procrastination, we wrote this paper. Much of our magnificent prose was ruthlessly eliminated by the editor to leave space for less important research.